Iron Supplementation in Suckling Piglets: An Ostensibly Easy Therapy of Neonatal Iron Deficiency Anemia - Mateusz Szudzik; Rafał R. Starzyński; Aneta Jończy; Rafał Mazgaj; Małgorzata Lenartowicz; Paweł Lipiński (MDPI AG, 2018)
In pigs, iron deficiency anemia (IDA) is the most prevalent deficiency disorder during the early postnatal period, frequently developing into a serious illness. On the other hand, in humans, only low-birth-weight infants, including premature infants, are especially susceptible to developing IDA. In both human and pig neonates, the initial cause of IDA is low birth iron stores. In piglets this shortage of stored iron results mainly from genetic selection over the past few decades for large litter sizes and high birth weights. As a consequence, pregnant sows cannot provide a sufficient amount of iron to the increasing number of developing fetuses. Supplementation with iron is a common practice for the treatment of IDA in piglets. For decades, the preferred procedure for delivering iron supplements during early life stages has been through the intramuscular injection of a large amount of iron dextran. However, this relatively simple therapy, which in general, efficiently corrects IDA, may generate toxic effects, and by inducing hepcidin expression, may decrease bioavailability of supplemental iron. New iron supplements are considered herein with the aim to combine the improvement of hematological status, blunting of hepcidin expression, and minimizing the toxicity of the administered iron. We propose that iron-deficient piglets constitute a convenient animal model for performing pre-clinical studies with iron supplements.